The Strategy of Developing Microfinance Program Implemented by PT Newmont Nusa Tenggara in Running Its Corporate Social Responsibility Program at West Sumbawa Regency - Bakhri, Syamsul; Sri Wahyuni, Ekawati; Muljono, Pudji (Sodality: Jurnal Sosiologi Pedesaan, 2015)
This research aims at (1) studying the microfinance program run by and the organization of Yayasan Olat Parigi/ Olat Parigi Foundation (YOP) as part of PT Newmont Nusa Tenggara’s Corporate Social Responsibility; (2) formulating the development strategy for the organization and microfinance program for self-reliance and sustainability. This study employs qualitative approach and supported by quantitative approach. The study shows that: Firstly, theorganizational management of YOP constitutes two periods of services namely YOP Part I and YOP Part II. In comparison, the organizional management and program run by YOP Part II is better than YOP Part I as demonstrated by a number of improvements in some aspects including management of administration, human resources, budgeting, microfinance program and business unit strategic. However, this study has identified weaknesses in the area of self-reliance, resilience, and sustainability as shown in high dependency of the foundation to PTNNT (both in financing and facilitation). The Microfinance program has been implemented as per applicable SOP where clients are facilitated to obtain easy access and capability to fulfill the requirements, simplified procedures, right on target, up to date, consistent with characteristics of the locals and most importantly it provides more benefits for the locals.A number of challenges identified in running the microfinance program include high number of Non-Performing Loan, limited financing scheme, and inadequate assistance and/or capacity to the program beneficiaries. Secondly, the development strategy for organizational and microfinance programs shall be improved to reach a self-reliance, resilience, and sustainability of the program through implementation of bounding, bridging, and creating/ networking strategies.Keywords: CSR,development strategy, institution, microfinance